2016
DOI: 10.18632/oncotarget.12223
|View full text |Cite
|
Sign up to set email alerts
|

The changing 50% inhibitory concentration (IC50) of cisplatin: a pilot study on the artifacts of the MTT assay and the precise measurement of density-dependent chemoresistance in ovarian cancer

Abstract: Inconsistencies in the half-maximal (50%) inhibitory concentration (IC50) data for anticancer chemotherapeutic agents have yielded irreproducible experimental results and thus reciprocally contradictory theories in modern cancer research. The MTT assay is currently the most extensively used method for IC50 measurements. Here, we dissected the critical reasons behind MTT-dependent IC50 inconsistencies. We showed that IC50 errors caused by the technical deficiencies of the MTT assay are large and not adjustable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 90 publications
(63 citation statements)
references
References 52 publications
4
55
1
3
Order By: Relevance
“…The results from the western blot analysis confirmed that glucosamine significantly inhibited STAT3 phosphorylation of CSCs and MCF7 cells to a similar degree. The less significant inhibitory effect of 4 mM glucosamine in ALDH + breast cancer cells may be due to the increased abundance of CSCs in ALDH + breast cancer cells, compared with MCF7 cells, which exerted a density-dependent effect on chemoresistance, as indicated by He et al (35). CSCs may also attempt to maintain their stemness by activating other pathways that contribute to STAT3 activation, including overactivation of the G-protein-coupled receptor signaling pathway or overexpression of gp130 (36).…”
Section: Discussionmentioning
confidence: 93%
“…The results from the western blot analysis confirmed that glucosamine significantly inhibited STAT3 phosphorylation of CSCs and MCF7 cells to a similar degree. The less significant inhibitory effect of 4 mM glucosamine in ALDH + breast cancer cells may be due to the increased abundance of CSCs in ALDH + breast cancer cells, compared with MCF7 cells, which exerted a density-dependent effect on chemoresistance, as indicated by He et al (35). CSCs may also attempt to maintain their stemness by activating other pathways that contribute to STAT3 activation, including overactivation of the G-protein-coupled receptor signaling pathway or overexpression of gp130 (36).…”
Section: Discussionmentioning
confidence: 93%
“…The concentrations of glucose (11.2 mM) and insulin (100 nM) administered to cultured ovarian cancer cells (HO8910, ES-2 and OVCAR-3) were comparable to the peak levels of blood glucose and insulin emerging between 0.5 and 1.0 h following 75-g oral glucose uptake. 26,27 We adopted a limiting dilution-modified clonogenic assay 5,25 to assess the 50% inhibitory concentrations (IC 50 s). A notable right-shift in the dose-response curves for both cisplatin and taxol was observed in cells pretreated with glucose and insulin for 1 h (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These findings can help to improve the current clinical limitations in ovarian cancer treatment, such as the delayed prediction of chemoresistance, a semiblind choice of chemotherapeutic agents, and thereafter, the loss of optimal treatment opportunities, which are frequently encountered by simply using tumor volume, IHC biomarkers or PDX models for evaluating or preventing chemoresistance. [4][5][6][7] CA125 has been a classical biomarker of ovarian cancer for over 30 years. However, few studies have focused on the significance of physiological/pathological fluctuations in this biomarker.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations